2009
DOI: 10.1167/iovs.08-2639
|View full text |Cite
|
Sign up to set email alerts
|

Birth Prevalence and Mutation Spectrum in Danish Patients with Autosomal Recessive Albinism

Abstract: TYR is the major OCA gene in Denmark, but several patients do not have mutations in the investigated genes. A relatively large fraction of patients were observed with AROA, and of those 52% had no mutations compared with 15% of those with OCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 27 publications
4
73
0
Order By: Relevance
“…There is the same distribution in this study as these three alleles account for 14,9,7 alleles respectively among the 48 identified TYR alleles (Table 1). Similarly, the most common mutational allele of SLC45A2 is p.D160H in this study, which is in agreement with our previous report [3].…”
Section: Common Alleles and Unusual Alleles In This Screensupporting
confidence: 68%
See 1 more Smart Citation
“…There is the same distribution in this study as these three alleles account for 14,9,7 alleles respectively among the 48 identified TYR alleles (Table 1). Similarly, the most common mutational allele of SLC45A2 is p.D160H in this study, which is in agreement with our previous report [3].…”
Section: Common Alleles and Unusual Alleles In This Screensupporting
confidence: 68%
“…However, the spectra of disease genes and mutational alleles of the known OCA genes vary in different populations. The distributional pattern of TYR, OCA2, SLC45A2 and HPS1 in the Chinese population [3] is apparently different from other populations such as Japanese [13], non-Hispanic Caucasians [9], and Danes [14]. Nevertheless, TYR is the most common OCA gene in all these four populations.…”
Section: Discussionmentioning
confidence: 79%
“…Patients with OCA show genetic heterogeneity and four subtypes have so far been identified in humans namely OCA1-4 [1,2]. OCA1 is due to mutations in the tyrosinase (TYR) gene, OCA2 is due to mutations in the P gene, OCA3 is due to tyrosinase-related protein 1 gene (TYRP1) mutations, and OCA4 is due to solute carrier family 45 member 2 (SLC45A2) mutations.…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism has also recently been reported in another albinism patient who also may have lacked nystagmus. 6 We present this case to emphasize that oculocutaneous albinism gene mutations can cause phenotypic variation not only in the presence and type of cutaneous findings but also in the severity and type of ocular disease. Ophthalmologists should, therefore, suspect and evaluate this diagnosis in patients with minimal or atypical ocular findings of albinism, such as apparently isolated foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 89%